Optimizing Human Capital: The Impact of Work-Life Balance on Organizational Outcomes Mediated by Commitment and Citizenship Behavior in Giriwoyo's Education Sector - Mardianti, Diah; Suprapti, Anastasia Riani (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of work-life balance (WLB) on organizational performance, with organizational commitment and Organizational Citizenship Behavior (OCB) as mediating variables in educators in Giriwoyo District, Wonogiri. This study uses a quantitative approach with data collected through an online questionnaire distributed to 150 respondents who are educators in Giriwoyo District. The results showed that work-life balance (WLB) has a positive and significant effect on organizational performance, both directly and through the mediation of organizational commitment and Organizational Citizenship Behavior (OCB). The findings provide valuable insights for school management and policy makers to improve educators' work-life balance, which in turn can improve overall organizational performance.